2019
DOI: 10.1029/2019ja026721
|View full text |Cite
|
Sign up to set email alerts
|

Superfountain Effect Linked With 17 March 2015 Geomagnetic Storm Manifesting Distinct F3 Layer

Abstract: The existence of an additional stratification in the daytime equatorial ionospheric F region (the F3 layer) was known since the 1940s. However, its characteristics and the underlying physical mechanism have been uncovered only recently. In this paper, we present and discuss the F3 layer characteristics observed by six ionosondes distributed over equatorial and low latitudes (−20° to +25° dip latitudes) in the Brazilian longitude sector during the strongest geomagnetic storm (DstMin = −223 nT) of solar cycle 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…However, in the same time interval, the ionograms (Figure 10) showed a transition from occurrences of Spread‐F at 08 UT (05 LT at 45°W, before sunrise) to a condition favorable enough to develop an F3 layer at 10 UT (07 LT at 45°W, after sunrise). Such a layer is especially clearly identified CGK21 (indicated with an arrow), in the upper border of the southern crest of the EIA, and has been reported in previous studies related to the Saint Patrick magnetic storm (Venkatesh et al, 2019). Over FZA0M, where DIX showed higher values, the ionograms reveled high altitude Spread‐F between 07:30 and 08:30 UT (05 LT at 45°W), when it is supposed to have no Spread‐F.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…However, in the same time interval, the ionograms (Figure 10) showed a transition from occurrences of Spread‐F at 08 UT (05 LT at 45°W, before sunrise) to a condition favorable enough to develop an F3 layer at 10 UT (07 LT at 45°W, after sunrise). Such a layer is especially clearly identified CGK21 (indicated with an arrow), in the upper border of the southern crest of the EIA, and has been reported in previous studies related to the Saint Patrick magnetic storm (Venkatesh et al, 2019). Over FZA0M, where DIX showed higher values, the ionograms reveled high altitude Spread‐F between 07:30 and 08:30 UT (05 LT at 45°W), when it is supposed to have no Spread‐F.…”
Section: Resultssupporting
confidence: 74%
“…The recovery phase has taken place at 22 UT on 17 March 2015, after the Dst reached −223 nT. On this complicated scenario, we may have several external drivers acting in the ionospheres, such as prompt penetration electric field (PPEF, C. M. M. Denardini et al, 2011; Forbes et al, 1995; Venkatesh et al, 2019) and disturbance dynamo electric field (DDEF, Blanc & Richmond, 1980; Nava et al, 2016; Nogueira et al, 2011). Indeed, Mansilla (2019) reported negative disturbances in foF2 after this storm commencement at low and mid‐low latitudes over Brazil, followed by positive disturbances in foF2.…”
Section: Resultsmentioning
confidence: 99%
“…An abrupt increase in the AE parameter together with incursion of the IMF Bz to negative values was observed on March 17 at around 0600 UT, followed by a decrease in the base height of the layer over the regions, featuring a PPEF (see the line labeled "PPEF" in Figure 1). The PPEF events during this magnetic storm were described by Batista et al (2017) and Venkatesh et al (2019). They showed that an eastward PPEF in the afternoon acted as the main driver for the F3 layer formation in the equatorial and low latitudes.…”
Section: The March 17 2015 Geomagnetic Storm: An Example Of a Case Studymentioning
confidence: 99%
“…Here, we chose this event as an example of the effects in Es layer dynamics over the Brazilian region during the disturbed periods. Our motivation to study this magnetic storm is that the response of the lower ionospheric parameters is concentrated in the D region (Maurya et al, 2018); TEC distribution (Astafyeva et al, 2015;Spogli et al, 2016;Venkatesh et al, 2017;Wu et al, 2016), F region (Batista et al, 2017;De Michelis et al, 2020;Venkatesh et al, 2017Venkatesh et al, , 2019, and in the space weather indices (Denardini et al, 2020). The St. Patrick's Day storm and its consequences on Es layers were not deeply studied yet as far as we know.…”
Section: The March 17 2015 Geomagnetic Storm: An Example Of a Case Smentioning
confidence: 99%
“…Since then, investigations related to the F3 layer have become an activate topic in the ionospheric study. Many researches have investigated the formation of ionospheric F3 layer over the equatorial and low‐latitude region with regard to its diurnal, seasonal, solar activity, and geomagnetic activity variations at different locations (e.g., Balan et al., 2000, 1998, 2008, 2011, 2018; Batista et al., 2002, 2017; Chaitanya et al., 2013; Hsiao et al., 2001; Jenkins et al., 1997; Klimenko, Klimenko, et al., 2012, Klimenko, Zhao, et al., 2012; Lin, Richmond, Bailey, et al., 2009; Lin, Richmond, Liu et al., 2009; Lynn et al., 2000; Paznukhov et al., 2007; Rama Rao et al., 2005; Sreeja et al., 2009, 2010; Tardelli & Fagundes, 2015; Tardelli et al., 2016; Thampi et al., 2007; Uemoto et al., 2011, 2006, 2007; Venkatesh et al., 2019, 2020, 2017; Zain et al., 2008; Zhao et al., 2005; Zhao, Wan, Reinisch, et al., 2011; Zhao, Wan, Yue, et al., 2011; Zhao et al., 2014; Zhu et al., 2013). From those studies, the general characteristics about the F3 layer are summarized as follows: (a) F3 layer generally occurs during the daytime (08:00–17:00 LT) within about ±10° geomagnetic latitudes, and become much evident in 10:00–14:00 LT. (b) F3 layer is frequently occurred on the summer side of the geomagnetic equator, especially under the solar minimum condition.…”
Section: Introductionmentioning
confidence: 99%